Majaz in Mutasybihat Verses from the Perspective of Salaf and Khalaf Ulama - ramadhani, Siti fadilah; Qomar, Subaidi (PT. Education Research Center, 2025)
This article examnes majaz in mutasyabihat verses in the Qur’an. There ara difference between the salaf and khalaf scholars regarding the issue of majaz. According to the salaf scholars, they rejected majaz in the Qur’an and left the meaning of mutasyabih verse to Allah to avoid tasybih or similarity. Meanwhile, the later scholars accepted majaz in the Qur’an so that these verses were not understood literally through interpretation. The research method used in writing this article is a qualitative method with a library approach and uses descriptive analysis of the verses of the Qur’an that contain majaz. The mutasyabihat verses include verses about the attributes of Allah and the muqataa’ah letters. The salaf scholars belived and trusted the mutasyabihat verses and left their true meaning to Allah, so that their meaning would be tanzih ( purification) and not cause tasybih (likening). Meanwhile, later scholars intrted the mutasyabihat verses so that they could be easily understood by the mind and did not cause misunderstanding. The majority of scholars from the firs to third centuries, namely the salaf, interpreted these letters as meaning that only Alah knows. Later, many scholar tried to interpret them as the names of surahs, or as a way for Allah to attract the attention of listeners.